Kedudukan Korban Tindak Pidana Dengan Kerugian Dibawah UMP Berdasarkan Undang-Undang Sistem Peradilan Pidana Anak (RechtJiva, 2024)
The provisions of article 9, paragraph (2) of the Criminal Justice System Act stipulate that there are certain conditions in which a different agreement does not require the consent of the victim and/ or the family of the child victim, one of which is when the value of the loss of victim does not exceed the minimum wage of the local province. (UMP). In each province has the size of the Provincial Minimum Wage (UMP) that is relatively different, then it is necessary to know about the basis of thinking of the formulation of the provisions of Article 9 paragraph (2) letter d and also the justice obtained by the victims under these provisions. The type of research used is a normative jurisprudence with a methodological approach to legislation. (statute approach). It was obtained an answer to the existing problem that based on the analysis carried out, according to the researchers there are some basis of thought that was the reason for the legislation making Provincial Minimum Wage (UMP) as a loss parameter in the Child Criminal Justice System Act i.e. First, it is based upon the existence of the Minimum Provincial Wage(UMP) itself; Second, the desire of legislation to expand the possibility of child offenders to obtain diversion; Third, the formulation of Article 9 paragraph (2) letter d, the selection of Provincial minimum wage (UP) is based on priority interests of the child. The provisions of article 9, paragraph (2) letter d of Law Number 11 of 2012 on the Child Criminal Justice System do not give the victim the opportunity to fully engage in the process itself. The child's criminal justice system in the settlement of crimes through the article indirectly seems to give the victim a position only as a witness. Furthermore, the provisions in the article are just impressed to box-up the victim's position that should be the same, either with losses above the Provincial Minimum Wage (UMP) or below it.